Publicity and Culture: the Audiovisual Advertisement for Polar Beer as a Micro-historical Feature and its Role as a Social Agent (London Journal of Research In Humanities and Social Sciences, 2024)
This article proposes an analysis of advertising as a social phenomenon that has an active participation in the identity and cultural construction of societies. To this end, it suggests that the advertising text and its consequent effects should be discussed and studied under the bias of micro-historical clippings, by Ginzburg (1989), in interface with assumptions of Patrick Charaudeau’s semiolinguistics. To operationalize this theoretical exercise, we selected as an analysis corpus an audiovisual advertising piece of Polar Beer 2014, when it launched cans commemorating the World Cup held in Brazil. As a complementary theoretical contribution, authors of publicity such as Gastaldo (2013), Solomon (2002) e Barthes (2001) were mobilized, in addition to concepts of culture, Hall (1999), regional identity, and Jacks (2003). As partial results, concrete elements are demonstrated that the advertisements of regional character, by using values and characteristics of regional cultures in their communication contracts, can be understood as micro-historical cuttings that contribute to the understanding of the formation of culture.
Keywords: Educational environment; risk factor; psychological vulnerability; psychological safety; psychological well-being of the environment; psychological stability.; Culture. Identity. Publicity. Advertising speech. Micro-history.